Phase I/II trial of local interstitial chemotherapy with arsenic trioxide in patients with newly diagnosed glioma - Han, Dayong; Teng, Lei; Wang, Xiaoxiong; Zhen, Yunbo; Chen, Xiaofeng; Yang, Mingchun; Gao, Ming; Yang, Guang; Han, Mingyang; Wang, Ligang; Xu, Jiajun; Li, Yue; et al. (Frontiers in Neurology, 2022)
Background: Glioma is the most common primary brain tumor in adults with poor prognosis. The glioma patients benefit from STUPP strategy, including maximum and safe resection and adjuvant radiotherapy and chemotherapy. Arsenic trioxide could inhibit various tumors. However, it is a challenge to evaluate the efficiency and safety of srsenic trioxide in glioma patients. Objective: The arsenic trioxide has the potent therapeutic effect on glioma. However, the safety and efficacy of local interstitial chemotherapy with arsenic trioxide in newly diagnosed glioma patients is unclear. Methods: All patients received partial or complete tumor resection and intraoperative implantation of Ommaya reservoirs followed by standard radiotherapy. Arsenic trioxide with the starting dose 0.3 mg was administered via an Ommaya reservoir catheter inserted into the tumor cavity for 5 consecutive days every 3 months for a total of eight cycles unless tumor progression or excessive toxicity was observed. Results: No hematological or grade 4 nonhematological toxicity was observed in any patient during arsenic trioxide treatment. The maximum tolerated dose of 1.5 mg of arsenic trioxide was safe and well tolerated. The median overall survival for WHO grade III glioma was 33.6 months, and for glioblastoma was 13.9 months. The median progression-free survival for WHO grade II glioma was 40.3 months, for grade III glioma was 21.5 months, and for glioblastoma was 9.5 months. Conclusion: These results suggest that arsenic trioxide is safe and well tolerated with local delivery into the tumor cavity of the brain, and the dose recommended for a phase II trial is 1.5 mg.